Impact of trade liberalization and world price changes in Bangladesh: a computable general equilibrium analysis - Mohammad Jahangir Alam; Jeroen Buysse; Ismat Ara Begum; Stephan Nolte; Eric J. Wailes; Guido Van Huylenbroeck (Agricultural and Food Economics, 2016)
The paper analyzes the impact of partial liberalization of trade and changes in world prices of agricultural commodities in Bangladesh using single country Computable General Equilibrium (CGE) model. Since the agricultural sector is sensitive to overall employment, household welfare and food security, the analysis focuses on the changes in agricultural production, consumption, household income and welfare. The results show that trade liberalization increases the welfare of all household groups while world market price increases decrease welfare. It means that although trade liberalization generates a welfare increase for households but this is dependent on the relative level of world commodity prices. Our results are based on the analysis of aggregate household groups, so it may be of future research interest to extend the model with more detailed household groups using a CGE-micro simulation approach.
Keywords: 330; Static; CGE; Trade policy; World prices; Agricultural commodities; Bangladesh